Risk factors for unanticipated hospitalizations in children and youth with spina bifida at an urban children's hospital: A cross-sectional study. Issue 1 (January 2023) - Smith, Kathryn A.; Hudson, Sharon M.; Betz, Cecily L.; Chwa, Jason S.; Cellura, Rhonda; Van Speybroeck, Alexander
Abstract: Background: Spina bifida (SB) is a condition resulting from the improper closure of the neural tube and vertebral column during fetal development. While patients' life expectancy and quality of life have improved dramatically due to medical advances, children continue to experience health-related issues that often require hospitalizations. Objective: The association among sociodemographic and clinical characteristics with potentially preventable hospitalizations (PPH) in children and youth with myelomeningocele type SB was investigated in this cross-sectional study. Methods: Chart reviews and data extraction were conducted on 108 children and youth, ages 1 month to 21 years, admitted for PPH in a regional children's academic medical center between May 2017 and July 2019. Sociodemographic variables included sex, age, type of insurance and ethnicity. Clinical variables included level of lesion, ambulation status, shunt dependency and selected diagnostic categories. Univariate, bivariate, and multivariate analyses were conducted to identify factors associated with PPH. Results: Factors associated with PPH included being male, ages 5–18 years, low lumbar level lesions, non-ambulatory, with public insurance, Hispanic and shunt dependent. Most hospitalizations (73%) were for neurologic or urologic conditions. Factors independently associated with PPH were ethnicity for urologic conditions, being ambulatory for metabolic conditions, and age for gastroenterology conditions. Conclusion: Selected demographic and clinical variables were found to be associated with PPH of children and youth with myelomeningocele-type SB. The most common reasons for PPH were shunt malfunctions and urinary tract infections, consistent with other studies.